PARP inhibitor reduces proliferation and increases apoptosis in breast cancer cells - Shi, Yan; Zhou, Fang; Jiang, Feng; Lu, Hong; Wang, Jianjun; Cheng, Chuanyao (Chinese Journal of Cancer Research; Vol 26, No 2 (April 26, 2014): Chinese Journal of Cancer Research, 2014)
Objective: Apoptosis is a reliable marker of chemotherapeutic efficacy. Olaparib and paclitaxel inhibit proliferation and induce apoptosis in a variety of cancers. We investigated the effects of paclitaxel combined with olaparib on apoptosis in breast cancer Bcap37 cells. Methods: Proliferation and apoptosis were detected by MTT assay and PI staining. Degradation of pro-caspase-3 and poly(ADP-ribose) polymerase (PARP) was analyzed by Western blotting. Results: Compared with paclitaxel alone, paclitaxel combined with 100 mg olaparib significantly reduced survival in Bcap37 cells at all tested treatment durations (P